Novel crystal forms of Entresto: a supramolecular complex of trisodium sacubitril/valsartan hemi-pentahydrate - Shaikh, Tabrez R.; George, Christy P.; Bhukya, Priyanka; Shelke, Nikita; Pawar, Komal; Garai, Abhijit; Dandela, Rambabu; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2022)
Entresto is a salt-cocrystal supramolecular complex with the chemical name trisodium sacubitril/valsartan hemi-pentahydrate for treating chronic heart failure and was approved by the US FDA in 2015. This multidrug complex was synthesized in our laboratory to investigate its polymorphic behavior. Different crystallization conditions, including various solvent systems, yielded different novel solid forms of Entresto (Form-I to Form-VI), including the reported form. All the novel solids are solvent-dependent and were reproducibly crystallized on a 10 g scale quantity. The 1H NMR spectra confirmed the 1 : 1 stoichiometry of the two drugs, namely, sacubitril and valsartan, in all the solid forms of the crystalline products. Powder X-ray diffraction and DSC analysis of the crystalline solids established that they are distinct crystalline forms. Stability studies under ambient conditions carried out over a one-year period showed higher stability for Form-I and Form-III compared to the other forms, including the innovator crystal form (labelled as Form-II). The novel crystal forms (notably Form-I and Form-III) exhibit higher stability and less hygroscopicity than the reported Form-II.